Evaluation of banana varieties for quality attributes - Sabeena Thajuddeen (Department of Home Science, College of Horticulture, 2000)
The study entitled "Evaluation of banana varieties for quality attributes" was undertaken to evaluate the quality characters and the nutritive value of the local banana varieties of different genomes. The banana varieties were evaluated for different quality characters like weight of bunch, weight of hands, number of hands, number of fingers in each hand and pulp/peel ratio. The results revealed that there was significant variation between the varieties in different quality characters. - Physical characters like colour of the fruit, colour of the pulp, weight and volume of the fruit, firmness of the fruit and pulp from the day of harvest were recorded. The weight, volume and firmness of the fruit and pulp decreased significantly on ripening. Most of the fruits had a yellow peel on ripening, the exceptions being Robusta and Red banana which had a light green and maronish brown colour on ripening. The banana varieties in the raw and ripe stages were analysed for moisture, total fibre, starch, calcium, phosphorus, iron, potassium and vitamin C. All the varieties in the raw stage were found to be high in starch and potassium. The calcium, phosphorus and iron contents were highest in Karpooravally whereas Red banana had the highest value for total fibre and potassium and Njalipoovan was high in starch and vitamin C. In the ripe stage Nendran was found to have the highest calcium, phosphorus and Beta carotene content. Except total fibre, all the other constituents of different varieties varied significantly in the raw and ripe stages. The starch and vitamin C content decreased significantly on ripening. Though there was a significant variation in the mineral content on ripening this change did not follow a specific pattern and varied depending upon the variety.